The 10 kb Drosophila virilis 28S rDNA intervening sequence is flanked by a direct repeat of 14 base pairs of coding sequence. - Rae, P M (1980)
Most repeat units of rDNA in Drosophila virilis are interrupted in the 28S rRNA coding region by an intervening sequence about 10 kb in length; uninterrupted repeats have a length of about 11 kb. We have sequenced the coding/intervening sequence junctions and flanking regions in two independent clones of interrupted rDNA, and the corresponding 28S rRNA coding region in a clone of uninterrupted rDNA. The intervening sequence is terminated at both ends by a direct repeat of a fourteen nucleotide sequence that is present once in the corresponding region of an intact gene. This is a phenomenon associated with transposable elements in other eukaryotes and in prokaryotes, and the Drosophila rDNA intervening sequence is discussed in this context. We have compared more than 200 nucleotides of the D. virilis 28S rRNA gene with sequences of homologous regions of rDNA in Tetrahymena pigmentosa (Wild and Sommer, 1980) and Xenopus laevis (Gourse and Gerbi, 1980): There is 93% sequence homology among the diverse species, so that the rDNA region in question (about two-thirds of the way into the 28S rRNA coding sequence) has been very highly conserved in eukaryote evolution. The intervening sequence in T. pigmentosa is at a site 79 nucleotides upstream from the insertion site of the Drosophila intervening sequence.